The trap bag concept of afterglow luminescence - Yih-Ping Huang (Nature Portfolio, 2017)
Abstract This article explains the behavior of afterglow luminescence using the trap bag concept, in which a constant phosphor dose contains a presumed bag with the ability to capture or release electrons through its opening. Luminescence is emitted as the bag releases the captured electrons. The electron-holding capacity is determined by the irradiation conditions, the width of the opening, and the electron activation; these factors are inherent properties of the long persistent luminescence (PLUM) dose and are affected by the thermal status. During the afterglow stage, higher temperatures may result in a wider opening and increased activation of electrons released from the bag, thus creating a higher light intensity and leading to the quicker exhaustion of the electrons within. In contrast, the opposite phenomenon will occur at lower temperatures. This article provides a detailed explanation of the trap bag concept at various thermal statuses and provides a method for delaying the afterglow peak profile through temperature change. Experimental tests were performed to confirm the proposed concept.